MENUMBUHKAN MORAL AGAMA MELALUI METODE MENDONGENG SAMBIL BERMAIN - Armanila Armanila; Riska Yanti; Fatimah Sitepu; Rahmayani Nasution; Eli Asni; Nabila Zahra; Ika Permatasari; Siti Mardiana (Journal of Innovative and Creativity, 2026)
Early childhood is a crucial period, often referred to as the "golden age," where children possess a remarkable ability to absorb values and behaviors from their environment. This community service aims to instill moral and religious values in students at RA Faturrahman through the "Storytelling while Playing" method. The background of this activity is the challenge of teaching abstract religious concepts to active children who often find one-way verbal instruction boring. The method used is a descriptive qualitative approach, utilizing the data analysis model by Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The results of this program demonstrate that integrating storytelling with interactive play significantly increases students' focus, enthusiasm, and understanding of moral messages. Through storytelling, children are introduced to positive role models, while the play sessions allow them to directly practice values such as honesty, empathy, and gratitude in a fun, pressure-free environment. The evaluation shows a positive shift in student behavior, where they become more active in social interaction and better at expressing moral values through simple actions. In conclusion, the storytelling while playing method is an effective and inspiring alternative for educators to build a strong character foundation and noble morals in children from an early age.